2010
DOI: 10.2214/ajr.09.3634
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Effective Dose to Pediatric Patients Undergoing Interventional Radiology Procedures Using Anthropomorphic Phantoms and MOSFET Dosimeters

Abstract: Patient doses during interventional procedures vary significantly depending on the type of procedure. User-friendly look-up tables may provide a helpful tool for health care providers in estimating effective doses for an individual procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…In a study using pediatric anthropomorphic phantoms Miksys et al showed that abdominal interventions carry the highest effective dose burden compared with chest and head/neck mock interventional procedures[21]. Effective dose results were in a range of 0.14 to 0.31mSv per minute of fluoroscopy in posterior-anterior beam direction, which is about one order of magnitude higher compared to our results.…”
Section: Discussioncontrasting
confidence: 71%
“…In a study using pediatric anthropomorphic phantoms Miksys et al showed that abdominal interventions carry the highest effective dose burden compared with chest and head/neck mock interventional procedures[21]. Effective dose results were in a range of 0.14 to 0.31mSv per minute of fluoroscopy in posterior-anterior beam direction, which is about one order of magnitude higher compared to our results.…”
Section: Discussioncontrasting
confidence: 71%
“…the introduction of pulsed fluoroscopy capability). For the majority of studies and procedures, dose assignment was based on institutional data applicable to the time period of our study [6][7][8][9][10]. Published values from the pediatric radiology literature [11][12][13][14][15][16][17][18][19] were used for the small number of examinations for which institutional data were not available.…”
Section: Methodsmentioning
confidence: 99%
“…Although we could not make an estimate for all age categories (blank fields in table 3), this did not pose a problem since the reason for the lack of data was the lack of patients in these age categories and for our study these data were not required. For cranial fluoroscopy procedures we used effective dose per minute estimates (1-year-old 0.028 mSv/min; 5-year-old 0.034 mSv/min; 10-year-old 0.022 mSv/min, after Miksys et al 24) and estimated total beam-on time of these procedures to be maximum 0.5 min.…”
Section: Methodsmentioning
confidence: 99%